(untitled) (Research, Society and Development, 2023)
There are currently 257 species of birds in Brazil, known to be classified as ’threatened with extinction’. In an attempt to solve this problem, several programs for the creation and propagation of birds in captivity, such as the Alagoas Curassow (Pauxi mitu), the Spix’s Macaw (Cyanopsitta spixii), among others, have been carried out in recent decades, with the in order to restore the maintenance of genetic diversity and restore wild populations of these species ex situ to later return them to their natural environment. However, captive breeding has a number of obstacles inherent in managing small, closed populations of endangered birds, including dealing with demographic instability, physical and behavioral deficiencies, sexual incompatibility, lack of synchrony and the need to maintain genetic diversity. Faced with this situation, artificial insemination (AI) biotechnology has the potential to contribute to helping solve some of these problems. In this context, this review aims to present and discuss the use of AI in non-domestic birds, to assist in the conservation of endangered species and to disseminate this biotechnology among breeders, technicians and professionals who work with bird reproduction.